The Role of Smart Solutions in Modeling the Security Problems of Water Resources in RA - Karapetyan, Tigran; Karapetyan, Aram (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2025)
The purpose of the work is to apply functions (investments and legal processes) aimed at reducing NRW in order to solve the problems of increasing the efficiency of water resources (drinking and irrigation water) supply and consumption. The object of the research is the water resources system of RA and its components. The subject of the research is the principles of water resources supply/management, economic-mathematical methods and models, which are aimed at assessing the increase of the efficiency of water resources supply and consumption with the help of system improvement.